(3LgO Gdebds - (3eMeO Hf YHO Gddg GdHZOGOj, TeS GdOjf GdJSJQjs
(3ChdgG (B:s
(3Chd GdeLdO GdChd (B: (3hHYO (B: (3aEf CVYa YHGO Gddg JYGdi eMeO GdJSJQi ,jbhd gPG eNJUQ ai GdWH , LeYJg ef cJH CQHGH GdUfGYg s
(3BNQgG (B:s
(3BNQ GdeLdO GdKGfi hZdW ef bGd (B: (3Ef GdJGaSjG gh UeZ GdTPGH GdLHdi hGdHQi s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B64 s
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK (B(2112) s
Keywords: (3GdWHs